Recombinant Human Platelet–Derived Growth Factor: A Systematic Review of Clinical Findings in Oral Regenerative Procedures. (April 2021) - Tavelli, L.; Ravidà, A.; Barootchi, S.; Chambrone, L.; Giannobile, W.V.
Aim: The use of recombinant human platelet-derived growth factor–BB (rhPDGF) has received Food and Drug Administration approval for the treatment of periodontal and orthopedic bone defects and dermal wound healing. Many studies have investigated its regenerative potential in a variety of other oral clinical indications. The aim of this systematic review was to assess the efficacy, safety, and clinical benefit of recombinant human platelet-derived growth factor (rhPDGF) use for alveolar bone and/or soft tissue regeneration. Material and Methods: Comprehensive electronic and manual literature searches according to the PRISMA guidelines were performed to identify interventional and observational studies evaluating the regenerative applications of rhPDGF-BB. The primary outcomes were the safety, efficacy, and overall clinical benefit of rhPDGF use in oral regenerative procedures. Results: Sixty-three human clinical studies (mean ± SD follow-up period of 10.7 ± 3.3 mo) were included in the qualitative analysis. No serious adverse effects were reported in any of the 63 studies, aside from the postoperative complications routinely associated with surgical therapy. Use of rhPDGF was shown to be beneficial when combined with allografts, xenografts, and alloplasts (the latter tricalcium phosphate [β-TCP]) for the treatment of periodontal defects and gingival recession. The use of rhPDGF also led to favorable clinical outcomes when combined with allografts or xenografts for guided bone regeneration (GBR) and alveolar ridge preservation. While favorable clinical results support the use of the combination of rhPDGF plus allograft or xenograft for GBR, ARP, and sinus floor augmentation, current data support the use of rhPDGF and alloplasts (e.g., β-TCP) only in periodontal defects and gingival recession. Conclusions: Based on the clinical evidence, rhPDGF is safe and provides clinical benefits when used in combination with bone allografts, xenograft, or β-TCP for the treatment of intrabony and furcation periodontal defects and gingival recession or when used with allografts or xenograft for GBR and ARP (PROSPERO CRD42020142446). Knowledge Transfer Statement: Clinicians should be aware that rhPDGF is a safe and effective approach for the treatment of intrabony and furcation periodontal defects and gingival recession or when used with allografts or xenograft for bone regeneration and alveolar ridge preservation. With consideration of cost and patient preference, this result could lead to more appropriate therapeutic decisions.